Role of yttrium in activation of 〈c + a〉 slip in magnesium: An atomistic approach. (November 2015) - Kim, Ki-Hyun; Jeon, Jong Bae; Kim, Nack Joon; Lee, Byeong-Joo
Graphical abstract: Abstract: The effect of Y addition on the slip behavior of an edge dislocation on basal, prismatic and second-order pyramidal slip planes of Mg has been investigated using a molecular dynamics simulation. It is found that Y increases the critical resolved shear stress of basal slip more than that of non-basal slip and eventually reduces the difference in the CRSS between different slip systems, which is proposed as the reason for the experimentally reported activation of 〈 c  +  a 〉 slip in Mg–Y alloys.